If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 5) + -3(x + -2) = 8x + 31 Reorder the terms: 9(5 + x) + -3(x + -2) = 8x + 31 (5 * 9 + x * 9) + -3(x + -2) = 8x + 31 (45 + 9x) + -3(x + -2) = 8x + 31 Reorder the terms: 45 + 9x + -3(-2 + x) = 8x + 31 45 + 9x + (-2 * -3 + x * -3) = 8x + 31 45 + 9x + (6 + -3x) = 8x + 31 Reorder the terms: 45 + 6 + 9x + -3x = 8x + 31 Combine like terms: 45 + 6 = 51 51 + 9x + -3x = 8x + 31 Combine like terms: 9x + -3x = 6x 51 + 6x = 8x + 31 Reorder the terms: 51 + 6x = 31 + 8x Solving 51 + 6x = 31 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 51 + 6x + -8x = 31 + 8x + -8x Combine like terms: 6x + -8x = -2x 51 + -2x = 31 + 8x + -8x Combine like terms: 8x + -8x = 0 51 + -2x = 31 + 0 51 + -2x = 31 Add '-51' to each side of the equation. 51 + -51 + -2x = 31 + -51 Combine like terms: 51 + -51 = 0 0 + -2x = 31 + -51 -2x = 31 + -51 Combine like terms: 31 + -51 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 6(2a+2)=24 | | 4a-(7-a)=2a-10 | | -2(3-4x)-7(x+2)= | | 4y+16=2r | | 16x-10=22 | | 8b-45=-40+7b | | 7(9-7(8-q))-9=9(7(9q-8)+6)-82 | | (5x+3y)(3x+5y)=0 | | 1=3(4k+3)-4k | | 20w-27=-11+19w | | 64.70=4.95+11.95x | | -2y-20=-4-3y | | 6v-2v=24 | | (x+6)(x-6)=28 | | 2v+8-5v=-28 | | 15x-16=33+14x | | 3x=4x+52 | | 16f+23=36+15f | | 5v-15=11+4v | | 2a-5=2a-3 | | 6w-17=27+5w | | 3x+1=5x-12 | | 2.5y+8.4=-20.6 | | 11z-26=-10+10z | | 2(2b-4)-3b=8-4(2-5b) | | 3x+8(2x-6)=2+14 | | A*9fora=2 | | 0.75*5x-x=8.25 | | 10a-9=43+9a | | -7(a-6)=7(a-4) | | -2z+13=45-3z | | -(4b-2)=18-2b |